Evaluation of load transfer behaviour of bored piles in residual soil incorporating construction effect - Zhu, Hong. (2008)
Large diameter bored piles are widely used in tropical and sub-tropical regions since they are well-suited for the support of heavy loads and for construction in residual soils and weathered rock formations. Traditional methods of design for piles which are primarily based on static formula using soil parameters derived from laboratory tests are not totally applicable mainly because laboratory measured parameters are often not representative of the in-situ properties and the load-settlement behaviour of bored piles are construction dependent. The local practice for the design of bored piles in residual soils needs to be carefully reviewed since the shaft friction contribution from the surrounding soils or rocks is often either totally neglected or wrongly estimated because of the deficiency in site investigation, insufficient consideration of construction effect, and lack of strong locally derived design correlations.